Clinical pharmacist prescriber in primary care in Slovenia: prospective non-randomised interventional study focused on clinical outcomes and quality of life - Stuhec, Matej; Kovacic, Alenka; Korpar, Marjetka; Banovic Koscak, Ana; Koder, Barbara; Mahoric, Dunja; Golubic, Spela Bernik; Gorup Cedilnik, Eva; Homar, Vesna; Stepanovic, Aleksandar; Rotar Pavlic, Danica (Frontiers in Pharmacology, 2025)
IntroductionClinical pharmacist prescribers in primary care settings and their impact on patient-reported outcomes (PROs) and clinical outcomes have not been described outside English-speaking countries.AimThe aim of this prospective interventional pilot study was to assess the impact of pharmacist prescribers on clinical results and patient-reported outcomes (PROs), while describing their development, evaluation, and implementation in Slovenia.MethodsThis prospective, 6-month, interventional, non-randomised study started in November 2024 and concluded in June 2025 in four primary care settings in Slovenia. Clinical pharmacists reviewed medications of patients and additionally prescribed medications based on the Collaborative Practice Agreement (CPA). In this process, they cooperated with patients and general practitioners (GPs). Only patients with an established diagnosis for selected non-communicable chronic conditions were included. The primary outcomes were changes in PROs, including quality of life (assessed via EQ-5D-VAS), and the Medication Appropriateness Index (MAI). Secondary outcomes included the prescription acceptance rate by GPs (percentage) and adherence to treatment guidelines. Tertiary outcomes involved the number of prescriptions that met the predefined clinical outcomes.ResultsThe study included 119 patients, with a mean age of 72.3 years (SD = 10.0). Quality of life improved from 63.6/100 (SD = 18.7) at baseline to 71.4/100 (SD = 15.9) at the end of the study (p = 0.000), with a corresponding QALY difference of 0.0252. The effect size (Cohen’s d) was 0.448 (95% CI: 0.084 to 0.812. The number needed to treat (NNT) was 4.0. During the study, clinical pharmacists prescribed 264 prescriptions to 119 patients, resulting in an acceptance rate of 91.3%. Adherence to treatment guidelines improved significantly (29.8% vs. 90.9%; p = 0.000). The effect size, expressed as an odds ratio (OR), was 25.7 (95% CI: 15.6–42.4). The number of prescriptions achieving the predefined clinical outcomes was significantly higher at the end of the study (70.8% vs. 6.4%; p = 0.000), with an OR of 33.9 (95% CI: 19.1–60.4). Deprescribing accounted for 25.3% of all protocols.ConclusionThis study demonstrates that prescriptions made by clinical pharmacists in collaboration with GPs, as specified in the CPA, improved PROs and clinical outcomes for predefined conditions.